Prävention des Delirs auf der Intensivstation - Braune, Stephan; Gurlit, Simone (DMW - Deutsche Medizinische Wochenschrift, 2019)
A delirium in patients in the intensive care unit (ICU) is a manifestation of a severe acute dysfunction of the brain. It has a high prevalence and is associated with a relevant increase in morbidity and mortality. A cholinergic deficit and dopaminergic overactivity are considered to be a cause of delirium. Polypharmacy, which is often present before admission to the ICU, especially in the elderly, plays a key role as a trigger. The knowledge and identification of risk factors for delirium is a precondition for the early and effective prevention of delirium. The aim is the pre-operative or pre-interventional optimization of modifiable risk factors. Early and effective prevention of delirium can improve clinical outcome, reduce mortality, and positively impact long-term functional outcome. Non-pharmacological measures are always the basis for the prevention of delirium: maintenance of the day-night rhythm, sleep promotion at night and stimulation during the day, involvement of relatives, the avoidance of dehydration and malnutrition, and others more. They are pharmacologically accompanied by an effective analgesia and a target and symptom-oriented sedation with well controllable, as little as possible delirogenic substances. Interdisciplinary and interprofessional cooperation is essential so that preventive concepts significantly reduce the risk of delirium, even in high-risk patients.
Keywords: Delir; Risikofaktoren; Prävention; Polypharmazie; Intensivmedizin